Amitriptyline, Pregabalin, and Gabapentin: Efficacy and Safety in Neuropathic Pain Treatment: A Single Center Study - Saad Ali, Zahid Khan, Zeeshan Ullah, Shakir Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pregabalin and gabapentin, two tricyclic antidepressants (TCAs), often treat NeP symptoms. Currently, these drugs are used to treat a disease known as neuropathic pain (NeP). Today, neuropathic pain treatment generally falls short of expectations. Methods: This single-center study was conducted in territory care hospital Lrh Peshawar from February 2021 to February 2022. Pregabalin and gabapentin, two tricyclic antidepressants (TCAs), are often used to treat NeP symptoms. Currently, these drugs are used to treat a disease known as neuropathic pain (NeP). Today, neuropathic pain treatment generally falls short of expectations. Results: “At two months, Group A had a mean NPRS score of 03.70, Group B of 03.61, and Group C of 05.20. The p-value was [0.001], and the statistically significant F-value was 06.61. Group 03 participants saw a significant difference between themselves and the other two treatment groups. The 11 patients in group B (24%) reported significantly more negative side effects, such as dizziness, as compared to the 04 patients (13%) in group A and the four patients (04.37%) in group C [p=0.040]. Sedation was present in 14 patients in group B (31.17%), which was a significant increase from group A's 23 patients (25%) and group C's 22 patients (23%) [P=0.035].” Conclusions: Among those with [NeP] As a consequence, 03 drug classes [gabapentine], [pregabaline], and [amitriptyline], each had an identical impact on NeP pain management. Regarding the Numeric Pain Rating Scale (NPRS) score, pregabalin performs better than gabapentine and amitriptyline. Since gabapentin has less long-term adverse effects than other medications, patient compliance is greater. Keywords: Neuropathic pain, gabapentine, amitriptyline, pregabalin